The Influence of the Law-and-Order Model in the Spanish Juvenile Criminal Law-Making Policy - García-Magna, Débora (Springer Nature, 2021)
The criminal law-and-order model, which appears to be displacing the procedural justice model in Spain, also influences the juvenile criminal system. The latest reforms in this field are a clear indicator of some of the features of the new model. The law that regulates criminal liability of minors in Spain has been modified several times (even before entering into force). The main argument for some of these reforms was the social feeling of impunity. Under the pretext of calming this social concern and even though there was not an upward trend in juvenile violent delinquency, the Spanish legislator hardened the response towards both serious and less serious crimes committed with violence or intimidation. In a clear reference to the retributive nature of the criminal sanction, the legislator mentioned the need to combine the best interests of the minor with the principle of proportionality. The main objective of this research is to undertake a critical analysis of the legislator’s discourse in this field. A confrontation with reality of data on public opinion and crime, and existing empirical investigations on the effectiveness of law has been carried out. The aim is to identify some examples of the irrationality of juvenile criminal law-making policy in Spain.
Política de acceso abierto: https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Delincuencia juvenil - Derecho y legislación; Jóvenes delincuentes; Criminal law-making policy; Juvenile criminal system; Empirical law evaluation; Irrationality in law making policy; Law-and-order model